2011
DOI: 10.1039/c0nr00555j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale morphology dependent pseudocapacitance of NiO: Influence of intercalating anions during synthesis

Abstract: Three nano-porous NiO samples with high specific surface area were prepared by a simple hydrothermal method under homogeneous precipitation conditions using CTAB as a template and urea as the hydrolysis controlling agent. This study was done to determine the effect of different anions (acetate, nitrate and chloride) present in the precursor salts on the morphology and pseudocapacitance behavior of NiO. The samples were characterized by thermogravimetry (TG), differential scanning calorimetry (DSC), powder X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(207 citation statements)
references
References 64 publications
(74 reference statements)
5
200
1
1
Order By: Relevance
“…In the present study the specific capacitance values were found to be ~10 % higher as compared to their work [15]. The higher values of specific capacitance can be attributed to the fact that the amorphous nature of the electrodes facilitates more bulk interaction which in turn increases the material utilization [34]. This involvement of the bulk was confirmed from the Wang et al model as shown in Fig.…”
Section: (7)supporting
confidence: 82%
“…In the present study the specific capacitance values were found to be ~10 % higher as compared to their work [15]. The higher values of specific capacitance can be attributed to the fact that the amorphous nature of the electrodes facilitates more bulk interaction which in turn increases the material utilization [34]. This involvement of the bulk was confirmed from the Wang et al model as shown in Fig.…”
Section: (7)supporting
confidence: 82%
“…The formation of urchin and sheaf-like hierarchical morphologies seems to depend strongly on the temperature of the reaction mixture under hydrothermal conditions. The formation of such surface hierarchical morphologies at different reaction temperatures is governed by a number of factors which include van der Waals forces, hydrogen bonding, hydrophobic attraction, crystal field attraction, electrostatic and dipolar fields, intrinsic crystal contraction and Ostwald ripening [58,59]. The other parameters that would influence significantly the shapes, orientations, growth of crystallites and the final morphology of materials are the energetics and kinetic aspects [60].…”
Section: Tga and Pxrdmentioning
confidence: 99%
“…Therefore NiCoO-120-cal sample is relatively better in charge storage performance and higher capacitance than NiCoO-200-cal sample. The specific capacitance was calculated from the discharge curves at different current densities using following equation [13,59]:…”
Section: Chronopotentiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of morphology on supercapacitor property of the anode has been investigated using other materials, a clear relationship between the morphology and property has not been established. 31,38 It is well known that the morphologies of Cu 2 O play a vital role in their physical and chemical properties. 39,40 Therefore, in this study, different morphologies of Cu 2 O were synthesized via a hydrothermal method to examine the effects of morphology on the supercapacitor properties.…”
Section: -31mentioning
confidence: 99%